PENGARUH LATAR BELAKANG PENDIDIKAN DAN PENGALAMAN POLITIK TERHADAP KINERJA DPRD DALAM PENGAWASAN PENGELOLAAN KEUANGAN DAERAH/APBD - Nuru, Ferdinant; Mawikere, Lidya (Universitas Sam Ratulangi, 2013)
This study aimed to examine the effect of level of education and political experience to Performance Oversight Council in Financial Management / Budget.The data used in this study is primary data and instruments in this study is a questionnaire that is processed using SPSS 19. The subjects were Sorong legislators who were 30. Of the 30 questionnaires distributed, returned and can be evaluated in a total of 29 questionnaires. The method used in this study is a multiple linear regression. To test the hypothesis used simultan eously F test and used partial eously t test.The results and hypothesis testing shows that the variables together education and political experience influence the performance of Parliament in monitoring the financial management area / budget. Partially only political experience that affect the performance of Parliament in monitoring regional financial management / budget, while the level of education does not affect the performance of the Council in the area of supervision of financial management / budget. Educational level was not affected due to lack of competence backed by councilors.Keywords: Level Of Education, Political Experience And Performance Oversight Council In Financial Management / Budget